Ruthenium(II)-Catalyzed C–H Allylation of N,N-Dialkylthiobenzamides with Allyl Methyl Carbonate by Sulfur Coordination - Wang, Runbao; Jin, Kun; Zhang, Rong; Li, Yaming; Duan, Chunying; Zhao, Liang (Synlett, 2024)
This report describes a Ru(II)-catalyzed C–H allylation of N,N-dialkylthiobenzamides with allyl methyl carbonate. The reaction is carried out using [RuCl2(p-cymene)]2 in the presence of Cu(OAc)2 and Ag2O. This method represents the first example of a Ru-catalyzed C–H allylation directed by a sulfur-containing group. As a further advantage, the method is performed in sustainable and ecofriendly MeCN as the solvent.
Keywords: C–H bond activation; directing group; ruthenium catalysis; allylation; thiobenzamides